2018
DOI: 10.1177/0040517518807450
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of moisture content effects on horizontal flame spread over thin cotton fabric

Abstract: In this paper, moisture content effects on horizontal flame spread were experimentally investigated using 0.245 mm thick, 28 cm tall and 28 cm wide untreated cotton fabric sheets with various moisture contents varying from 0 to 34%. The pyrolysis spread rates, flame heights and ignition times were obtained and analyzed. The corresponding results are as follows: as moisture content increases, the flame height and spread rate first increase and then decrease. In contrast, the ignition time shows an opposite tren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Gao et al. 32 confirmed that the fire spread rate of cotton fabric is about 2.9 mm/s. The FSV of the nonwoven samples was higher than that of the thin cellulose paper under all the working conditions tested in the current work.…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations
“…Gao et al. 32 confirmed that the fire spread rate of cotton fabric is about 2.9 mm/s. The FSV of the nonwoven samples was higher than that of the thin cellulose paper under all the working conditions tested in the current work.…”
Section: Resultsmentioning
confidence: 95%
“…In addition, Avinash et al 42 showed a FSV of 17 mm/s when cellulose paper was placed at an inclination angle of less than 20 . Gao et al 32 confirmed that the fire spread rate of cotton fabric is about 2.9 mm/s. The FSV of the nonwoven samples was higher than that of the thin cellulose paper under all the working conditions tested in the current work.…”
Section: Flame Spread Ratementioning
confidence: 95%
See 2 more Smart Citations
“…Numerous textile applications of infrared thermography can be found in the literature, including measuring energy dissipation during stretching, fabric radiant thermal conductivity, spreading of pyrolysis during combustion, and smoldering ignition in upholstery fabrics. [1][2][3][4] All of these thermographic measurement methods are dependent on the apparent emissivity of the measurement targets. Emissivities for a number of materials are given in literature, and those of some fabrics have been reported by Zhang et al and Brown and Young.…”
mentioning
confidence: 99%